Postcoital Internal Carotid Artery Dissection Presenting as Isolated Painful Horner Syndrome: A Case Report - Eren Gozke; Hilal Tastekin Toz; Pınar Kahraman Koytak; Funda Alparslan (Case Reports in Neurological Medicine)
Postcoital artery dissection is a rare condition. Here we report a 40-year-old male patient with painful Horner syndrome related to postcoital internal carotid artery (ICA) dissection. In neurologic examination of the patient, semiptosis, enophthalmus, and myosis were observed on the left side. There were no carotid bruits. On T1-weighted and fat-suppressed cranial MRI, hyperintensity consistent with intramural hematoma was observed within cervical and temporal petrous segments of left ICA. On cervical and cranial MRA, marked decrease in the calibration of C1 and C2 segments of the left ICA was remarkable. The patient was diagnosed as left ICA dissection and anticoagulant therapy was initiated. A prominent improvement was noted in clinical findings during two months of followup period.